Kepatuhan Syariah dalam Perbankan Online dan Fintech Syariah: Pembiayaan Online pada Prinsip-Prinsip Syariah - Muhammad Yudha Ardiansyah; Muhamad Zen (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
Financial technology (fintech) services in Indonesia are growing rapidly, including sharia fintech that operates based on sharia principles. DSN-MUI Fatwa No. 117/DSN-MUI/IX/2018 is the operational basis for sharia fintech, although the Financial Services Authority (OJK) has not fully integrated it into binding regulations. This study examines sharia compliance in sharia fintech services using library research methods. The results of the study indicate that although sharia fintech has grown, stronger legal instruments are needed so that sharia compliance is implemented comprehensively. The role of the Sharia Supervisory Board (DPS) is very important in ensuring that sharia principles are implemented. However, supervision and legal protection for sharia fintech consumers are still minimal. Therefore, special regulations and strengthening of the DPS function are needed to ensure that sharia fintech truly complies with Islamic legal principles, maintains the existence of fintech, and increases consumer trust.